The Influence of Product Attributes, Brand Image, and Service Qualityon Digital Marketing Mediated Purchasing Decisions - Ainu Anggara; Nurul Badriyah; Titin Titin (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the influence of product attributes, brand image, and service quality on purchase decisions mediated by digital marketing at car showrooms in Lamongan Regency. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method using the SmartPLS application. Data was collected from 194 respondents who were car buyers consumers at 25 car showrooms in Lamongan Regency using purposive sampling techniques. The results showed that: (1) product attributes had a positive and significant effect on purchase decisions (T-statistic = 2,997; P = 0.003); (2) brand image has a positive and significant effect on purchase decisions (T-statistic = 2,231; P = 0.026); (3) service quality has a positive and significant effect on purchasing decisions (T-stats = 2,719; P = 0.007); (4) digital marketing has a positive and significant effect on purchasing decisions (T-statistic = 3,947; P = 0.000); (5) product attributes have a significant effect on digital marketing (T-stats = 4,861; P = 0.000); (6) brand image has a significant effect on digital marketing (T-stats = 10,122; P = 0.000); (7) service quality has a significant effect on digital marketing (T-statistic = 2,680; P = 0.008). In addition, digital marketing has been proven to partially mediate the relationship between product attributes, brand image, and service quality to purchase decisions. The R-Square value for digital marketing is 0.834 and the purchase decision is 0.881, indicating that the model has strong predictive power.